Penggunaan Game Edukatif Digital dalam Meningkatkan Minat Belajar Sejarah Siswa - Darojat, Muhammad Miftachul; Romadi (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to determine the use of digital educational games in increasing students' interest in learning history at SMA Negeri 1 Tuntang. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation during the learning process. The results of the study indicate that the use of digital educational games can create a more enjoyable learning atmosphere, increase active student participation, and foster enthusiasm in understanding historical material. In addition, students showed higher engagement through discussions, collaboration, and responses to challenges presented in the game. Thus, digital educational games can be an effective alternative learning media to increase interest in learning history while supporting innovative and student-centered learning. The conclusion of this study shows that digital educational games can be an effective learning innovation in increasing students' interest in learning history and supporting the creation of more participatory and relevant learning with technological developments in the digital era. Keywords: Digital Educational Games, History Learning, Learning Innovation Learning Interest.